High-hydroxyl quartz glass as well as preparation method and application thereof
Quartz glass prepared by axial vapor deposition method and secondary sintering method solves the problem of uneven hydroxyl group distribution in the prior art, realizes uniform hydroxyl group distribution and high performance of quartz glass, and is suitable for applications in high-tech fields.
Patent Information
- Application Number
- CN202510065840.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-03-21
AI Technical Summary
The lack of uniformity of hydroxyl groups in existing quartz glasses affects its mechanical strength, thermal expansion behavior, chemical stability and predictability, especially in applications in high-tech fields.
Quartz glass is prepared by axial vapor deposition method and secondary sintering method. By controlling the inlet flow rate of the silicon source, the inlet flow rate of water vapor and the sintering conditions, it is ensured that the hydroxyl group is evenly distributed in the axial and radial directions of the quartz glass.
It realizes uniform hydroxyl distribution of quartz glass in the axial and radial directions, improves its mechanical strength, consistent thermal expansion behavior, chemical stability and predictability, making it suitable for special experimental instruments, aerospace, ultraviolet energy transmission and nuclear power radiation resistance fields.
Smart Images

Figure CN119661065A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a quartz preparation technology, and in particular to a high-hydroxy quartz glass and a preparation method and application thereof. Background Art
[0002] Quartz glass is a single-component glass of SiO2. It has the advantages of high purity, wide spectral transmittance, chemical stability, resistance to thermal shock, high temperature deformation, radiation resistance, and electrical insulation. It is widely used in the fields of electric light sources, metallurgy, chemical industry, electronics, optical fiber, laser, aerospace, and nuclear technology. The hydroxyl content in quartz glass will affect its bonding structure, which will further affect its performance. For example, the presence of hydroxyl in quartz glass has a significant effect on the thermal stability, optical properties, and mechanical properties of the material.
[0003] Among them, the uniformity of hydroxyl groups restricts the application of quartz glass. The uniform distribution of hydroxyl groups helps to maintain the consistency of the mechanical strength of quartz glass and reduce the risk of cracks or breakage caused by local stress concentration; it can make quartz glass have more consistent thermal expansion behavior during heating or cooling, reducing the risk of thermal stress and thermal shock. At the same time, in chemical processing or high-temperature environments, the uniform distribution of hydroxyl groups can improve the chemical stability of quartz glass, thereby reducing local corrosion or degradation; in the manufacturing and processing process, the uniform distribution of hydroxyl groups can also improve the predictability and consistency of materials, thereby reducing processing defects and improving product qualification rate. In addition, in application fields that require high precision and high reliability, the uniform distribution of hydroxyl groups makes the performance of quartz glass more predictable and convenient for design and engineering applications. At present, with the widespread application of quartz glass in high-tech fields such as precision instruments, aerospace, ultraviolet energy transmission, and nuclear power radiation resistance, how to make quartz glass have uniformly distributed hydroxyl groups has become a problem that researchers in this field need to solve urgently. Summary of the invention
[0004] The present invention provides a quartz glass having uniform hydroxyl distribution in both axial and radial directions, thus having high stability and predictability, and being applicable to high-tech fields such as special experimental instruments, aerospace, ultraviolet energy transmission, nuclear power radiation resistance, etc.
[0005] The present invention discloses a method for preparing the above-mentioned quartz glass, which adopts an axial vapor deposition method and a secondary sintering method, thereby greatly improving the production efficiency while ensuring uniform distribution of hydroxyl groups, and facilitating subsequent mass production.
[0006] The present invention also provides an application of the above-mentioned quartz glass or the quartz glass prepared by the above-mentioned preparation method in the fields of special experimental equipment, aerospace, ultraviolet energy transmission, and nuclear power radiation resistance.
[0007] The present invention provides quartz glass, wherein the difference in hydroxyl content of the quartz glass in the axial direction is ≤100 ppm, and the difference in hydroxyl content of the quartz glass in the radial direction is ≤100 ppm.
[0008] The quartz glass as described above, wherein the hydroxyl content of the quartz glass is ≥750 ppm.
[0009] The present invention provides a method for preparing the above-mentioned quartz glass, which comprises the following steps:
[0010] Step 1, introducing saturated water vapor and a mixed gas of silicon source, hydrogen, oxygen and argon into a deposition chamber, and depositing a quartz target rod using an axial vapor deposition method to obtain a powder rod;
[0011] Step 2, performing a first sintering on the powder rod in a mixed atmosphere of saturated water vapor and oxygen, and performing a second sintering on the powder rod in a mixed atmosphere of saturated water vapor, oxygen and helium to obtain quartz glass;
[0012] In step 1, the flow rate of the silicon source is 20-60 g / min and the flow rate is 1.0-2.0 mm / s;
[0013] In step 1, saturated water vapor is introduced into the deposition chamber through a water mist torch; the angle formed between the axis of the water mist torch and the ground plane is α, and α is 30°-55°;
[0014] In step 1, the mixed gas is introduced into the deposition chamber through a deposition torch; the distance from the deposition torch mouth to the intersection of the deposition torch axis and the quartz target rod axis is L, in m, the silicon source introduction flow rate is v, in mm / s, and the numerical relationship between L and v satisfies L=(0.05-0.3)×v; preferably, L is 0.05-0.6 m;
[0015] In step 2, the flow rate of saturated water vapor in the first sintering is Q1, in L / min; preferably, Q1 is 10-80 L / min; the flow rate of saturated water vapor in the second sintering is Q2, in L / min, and the speed increase of the flow rate is k2, in L / min. min; the second sintering is divided into a heating stage and a constant temperature stage. The heating time of the heating stage is t, in min; Q2, Q1, k2 and The numerical relationship of t satisfies Q2=Q1+k2× t.
[0016] The preparation method as described above, wherein the deposition conditions include: a pressure of 0.5-3 Pa; and / or,
[0017] The first sintering conditions include: a temperature of 400-800° C., a pressure of 100-300 Pa, and a time of 24-72 hours; and / or,
[0018] The conditions of the second sintering include: the temperature in the constant temperature stage is 1250-1500° C., the pressure is 3-5 Pa, and the time is 4-8 hours.
[0019] The preparation method as described above, wherein in step 1, the flow rate of saturated water vapor is 10-50 L / min; and / or,
[0020] In step 1, the flow rate of hydrogen is 60-110 L / min; and / or,
[0021] In step 1, the oxygen flow rate is 30-120 L / min; and / or,
[0022] In step 1, the flow rate of argon gas is 10-15 L / min; and / or,
[0023] In step 2, the flow rate of helium in the second sintering is 10-50 L / min.
[0024] The preparation method as described above, wherein in step 2, the speed increase of the flow rate of saturated water vapor in the second sintering is k2, in units of L / min min; the heating rate in the second sintering is k1, in °C / min; the numerical relationship between k2 and k1 satisfies k2=(1.2-1.5)×k1;
[0025] Preferably, k1 is 2-5°C / min, k2 is 2.4-7.5 L / min min.
[0026] In the preparation method as described above, in step 1, the horizontal angle between the water mist torch and the deposition torch is θ, and θ is 30°-150°; preferably, θ is 30°-120°.
[0027] The preparation method as described above, wherein in step 1, depositing the quartz target rod using the axial vapor deposition method further comprises setting the rotation speed of the quartz target rod to 5-30 r / min; and / or,
[0028] In step 1, depositing the quartz target rod by using the axial vapor deposition method also includes setting the lifting speed of the quartz target rod to 30-100 mm / h.
[0029] In the preparation method as described above, in step 1, the diameter of the powder particles on the powder rod is 40-140 nm.
[0030] The present invention also provides an application of the above-mentioned quartz glass or the quartz glass prepared by the above-mentioned preparation method in the fields of special experimental equipment, aerospace, ultraviolet energy transmission, and nuclear power radiation resistance.
[0031] The present invention provides a quartz glass, which has a hydroxyl content difference of ≤100 ppm in the axial direction and a hydroxyl content difference of ≤100 ppm in the radial direction, and has a uniform hydroxyl distribution in both the axial and radial directions, and the uniform hydroxyl distribution helps to maintain the consistency of the mechanical strength of the quartz glass, and reduce the risk of cracks or breakage caused by local stress concentration; it can make the quartz glass have a more consistent thermal expansion behavior during heating or cooling, and reduce the risk of thermal stress and thermal shock. At the same time, in chemical processing or high-temperature environment, the uniform hydroxyl distribution can improve the chemical stability of the quartz glass, thereby reducing local corrosion or degradation; in the manufacturing and processing process, the uniform hydroxyl distribution can also improve the predictability and consistency of the material, thereby reducing processing defects and improving the product qualification rate. In addition, in the application field requiring high precision and high reliability, the uniform hydroxyl distribution makes the performance of the quartz glass more predictable, which is convenient for design and engineering application. Therefore, the quartz glass of the present invention can be applied to high-tech fields such as special experimental instruments, aerospace, ultraviolet energy transmission, and nuclear power radiation resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A schematic diagram of a deposition device according to an embodiment of the present invention;
[0033] Figure 2 A longitudinal view showing an angle α formed between the axis of the water mist spray lamp 5 and the ground plane according to an embodiment of the present invention;
[0034] Figure 3 It is a cross-sectional view of the horizontal angle θ between the water mist torch 5 and the deposition torch 7 according to an embodiment of the present invention;
[0035] Figure 4 A schematic diagram of a sintering device according to an embodiment of the present invention;
[0036] Figure 5 is a temperature-time curve diagram of the sintering step in Example 1;
[0037] Figure 6 The saturated water vapor flow-time curve and the sintering temperature-time curve of the sintering step in Example 1;
[0038] Figure 7 This is a graph showing the test results of the hydroxyl content of the quartz glass rod in Example 1;
[0039] Figure 8 This is a graph showing the test results of the hydroxyl content of the quartz glass rod in Example 2;
[0040] Fig. 9 This is a graph showing the test results of the hydroxyl content of the quartz glass rod in Example 4;
[0041] Fig.10 This is a graph showing the test results of the hydroxyl content of the quartz glass rod in Comparative Example 1;
[0042] Fig.11 This is a graph showing the test results of the hydroxyl content of the quartz glass rod in Comparative Example 2;
[0043] Fig.12 This is a graph showing the test results of the hydroxyl content of the quartz glass rod in Comparative Example 3;
[0044] Description of reference numerals:
[0045] 1: Quartz target rod;
[0046] 2: Powder stick;
[0047] 3: deposition chamber;
[0048] 4: Fixed end;
[0049] 5: Water mist torch;
[0050] 6: first exhaust pipe;
[0051] 7: Deposition torch;
[0052] 8: Raw material pipeline opening;
[0053] 9: Argon gas channel opening;
[0054] 10: Hydrogen channel opening;
[0055] 11: Oxygen channel opening;
[0056] 12: Pressure gauge;
[0057] 13: Fixed end of the boom;
[0058] 14: Sealing ring;
[0059] 15: second exhaust pipe;
[0060] 16: first air supply pipeline;
[0061] 17: Upper furnace body;
[0062] 18: spacer;
[0063] 19: The third exhaust pipe;
[0064] 20: graphite resistor;
[0065] 21: sintering furnace;
[0066] 22: Second air supply pipeline. DETAILED DESCRIPTION
[0067] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0068] A first aspect of the present invention provides quartz glass, wherein the difference in hydroxyl content of the quartz glass in the axial direction is ≤100 ppm, and the difference in hydroxyl content of the quartz glass in the radial direction is ≤100 ppm.
[0069] In the present invention, a Fourier infrared tester is used to test the hydroxyl content of the obtained quartz glass, and a point is set every 100 mm from the bottom to the top along the axial direction of the quartz glass rod, and 3 points are evenly tested from the point to the edge in the radial direction. After experimental verification, the hydroxyl content difference of the quartz glass of the present invention in the axial direction is ≤100 ppm, and the hydroxyl content difference of the quartz glass in the radial direction is ≤100 ppm. Among them, the hydroxyl content difference in the axial direction refers to the difference obtained by subtracting the minimum value of the hydroxyl content at different points of the quartz glass rod in the axial direction; the hydroxyl content difference in the radial direction refers to the difference obtained by subtracting the minimum value of the hydroxyl content at different points of the quartz glass rod from the center to the edge in the same radial direction.
[0070] The quartz glass of the present invention has a uniform hydroxyl distribution in both the axial and radial directions, and the uniform hydroxyl distribution helps to maintain the consistency of the mechanical strength of the quartz glass, reducing the risk of cracks or breakage caused by local stress concentration; it can make the quartz glass have a more consistent thermal expansion behavior during heating or cooling, reducing the risk of thermal stress and thermal shock. At the same time, in chemical processing or high-temperature environments, the uniform hydroxyl distribution can improve the chemical stability of the quartz glass, thereby reducing local corrosion or degradation phenomena; in the manufacturing and processing process, the uniform hydroxyl distribution can also improve the predictability and consistency of the material, thereby reducing processing defects and improving the product qualification rate. In addition, in application fields that require high precision and high reliability, the uniform hydroxyl distribution makes the performance of the quartz glass more predictable, which is convenient for design and engineering applications. Therefore, the quartz glass of the present invention can be applied to high-tech fields such as special experimental instruments, aerospace, ultraviolet energy transmission, and nuclear power radiation resistance.
[0071] In the above technical solution, the quartz glass of the present invention also has a high hydroxyl content, and its hydroxyl content is ≥750ppm. High-hydroxy quartz glass has strong radiation resistance, especially can absorb short-wavelength ultraviolet light and specific wavelength infrared light, and is in demand in different fields such as special experimental equipment, aerospace, biomedicine, etc. At the same time, high-hydroxy quartz glass has a large dispersion value and can also be used in the fields of measuring spectrum, optical fiber gyroscope, Rayleigh scattering distribution measurement, etc.
[0072] The second aspect of the present invention provides a method for preparing the above-mentioned quartz glass, which requires using Figure 1 and Figure 4 The device shown is carried out.
[0073] Figure 1 Schematic diagram of a deposition device according to an embodiment of the present invention, comprising a quartz target rod 1, a powder rod 2, a deposition chamber 3, a fixed end 4, a water mist torch 5, a first exhaust pipe 6, a deposition torch 7, a raw material pipeline port 8, an argon channel port 9, a hydrogen channel port 10, an oxygen channel port 11 and a pressure gauge 12; the first exhaust pipe 6 is arranged above the deposition device; the upper end of the quartz target rod 1 is fixed to the fixed end 4 and placed in the deposition chamber 3; the raw material pipeline port 8, the argon channel port 9, the hydrogen channel port 10, and the oxygen channel port 11 are respectively connected to the deposition torch 7, and the deposition torch 7 is connected to the deposition chamber 3; the powder particles sprayed by the deposition torch 7 are coated on the quartz target rod 1 to form a powder rod 2; the water mist torch 5 is located above the deposition torch 7 and connected to the deposition chamber 3; the deposition chamber 3 is also connected to a pressure gauge 12. Figure 1 As shown in FIG. 1 , the distance from the nozzle of the deposition torch 7 to the intersection of the axial direction of the deposition torch 7 and the axial direction of the quartz target rod 1 is L.
[0074] Figure 2 for Figure 1 A partial picture of the schematic diagram of the deposition device shows a longitudinal view of the angle α formed by the axis of the water mist torch 5 and the ground plane according to an embodiment of the present invention, including a quartz target rod 1 and a water mist torch 5; wherein the quartz target rod 1 is perpendicular to the ground plane, and the angle α formed by the axis of the water mist torch 5 and the ground plane.
[0075] Figure 3 for Figure 1 A partial picture of the schematic diagram of the deposition device shows a cross-sectional view of the horizontal angle θ between the water mist torch 5 and the deposition torch 7 according to an embodiment of the present invention, comprising a quartz target rod 1, a powder rod 2, a water mist torch 5 and a deposition torch 7; wherein the powder particles sprayed by the deposition torch 7 are coated on the quartz target rod 1 to form the powder rod 2, and in the cross-sectional view, the angle formed by the axis of the water mist torch 5 and the axis of the deposition torch 7 is θ.
[0076] Figure 4This is a schematic diagram of a sintering device according to an embodiment of the present invention, comprising a powder rod 2, a suspension rod fixed end 13, a sealing ring 14, a second exhaust pipe 15, a first air supply pipe 16, an upper furnace body 17, a partition plate 18, a third exhaust pipe 19, a graphite resistor 20, a sintering furnace 21, and a second air supply pipe 22; the upper end of the powder rod 2 is fixed to the suspension rod fixed end 13 and placed in the upper furnace body 17; the sealing ring 14 is arranged above the upper furnace body 17; the second exhaust pipe 15 is arranged at the upper part of the side of the upper furnace body 17; the first air supply pipe 16 is arranged at the lower part of the side of the upper furnace body 17; the upper furnace body 17 is located above the sintering furnace 21, separated by a partition plate 18 in the middle; the exhaust pipe 19 is arranged at the upper part of the side of the sintering furnace 21; the second air supply pipe 22 is connected to the bottom of the sintering furnace 21; and a graphite resistor 20 is also arranged inside the sintering furnace 21.
[0077] The method for preparing quartz glass provided by the present invention comprises: Figure 1 and Figure 4 The device shown in the figure comprises the following steps:
[0078] Step 1, introducing saturated water vapor and a mixed gas of silicon source, hydrogen, oxygen and argon into a deposition chamber 3, and depositing a quartz target rod 1 by an axial vapor deposition method to obtain a powder rod 2;
[0079] Step 2, performing a first sintering on the powder rod 2 in a mixed atmosphere of saturated water vapor and oxygen, and performing a second sintering on the powder rod 2 in a mixed atmosphere of saturated water vapor, oxygen and helium, to obtain quartz glass;
[0080] In step 1, the flow rate of the silicon source is 20-60 g / min and the flow rate is 1.0-2.0 mm / s;
[0081] In step 1, saturated water vapor is introduced into the deposition chamber 3 through the water mist torch 5; the angle formed between the axis of the water mist torch 5 and the ground plane is α, and α is 30°-55°;
[0082] In step 1, the mixed gas is introduced into the deposition chamber 3 through the deposition torch 7; the distance from the nozzle of the deposition torch 7 to the intersection of the axis of the deposition torch 7 and the axis of the quartz target rod 1 is L, in m, the flow rate of the silicon source is v, in mm / s, and the numerical relationship between L and v satisfies L=(0.05-0.3)×v; preferably, L is 0.05-0.6 m;
[0083] In step 2, the flow rate of saturated water vapor in the first sintering is Q1, in L / min; preferably, Q1 is 10-80 L / min; the flow rate of saturated water vapor in the second sintering is Q2, in L / min, and the speed increase of the flow rate is k2, in L / min. min; the second sintering is divided into a heating stage and a constant temperature stage. The heating time of the heating stage is t, in min; Q2, Q1, k2 and The numerical relationship of t satisfies Q2=Q1+k2× t.
[0084] In detail, in step 1 of the present invention, a powder rod 2 is obtained by depositing a quartz target rod 1 in a deposition chamber 3 using axial vapor deposition.
[0085] At present, the preparation of quartz glass generally adopts chemical vapor deposition method for deposition. This method cannot adjust the hydroxyl content from the initial stage, so it is difficult to control the uniformity of hydroxyl or increase the hydroxyl content. In addition, the deposition efficiency of chemical vapor deposition method is low and the deposition diameter is small, which easily leads to weak mass production effect. Therefore, in order to solve the above problems, the present invention uses axial vapor deposition method to prepare quartz glass.
[0086] The Vapour Axial Deposition (VAD) method uses a hydrogen-oxygen flame as a heat source to convert the raw material gas into glass powder, which is then dehydrated and sintered at high temperature to obtain a uniform and transparent core rod mother rod, and finally heated and stretched to form a VAD core rod of suitable size. The VAD process has advantages in the production of single-mode optical fiber preform core rods with simple cross-sectional structures due to its high deposition rate and flexible doping control. During the deposition process, the quartz target rod 1 is in the deposition chamber 3, which can isolate the quartz target rod 1 from the external gas and prevent it from being contaminated by free impurities in the surrounding environment during the deposition process.
[0087] In the axial vapor deposition method, saturated water vapor and a mixed gas of silicon source, hydrogen, oxygen and argon need to be introduced into the deposition chamber 3.
[0088] The silicon source may be a chloride of silicon or organic silicon, such as SiCl4 or CH3SiCl3; after being gasified, the silicon source may be mixed with hydrogen and oxygen, and hydrolyzed at high temperature to form a mist of SiO2, which is then sprayed onto the quartz target rod 1 through the deposition torch 7, thereby forming a powder rod 2. During this process, argon gas may also be introduced to prevent the silicon dioxide particles produced by deposition from accumulating at the lamp mouth of the deposition torch 7 and causing blockage, thereby playing an isolating role and depositing the torch 7.
[0089] In addition, flame deposition generates heat during the deposition process, resulting in the loss of water molecules in the powder rod 2. Therefore, the present invention can make up for the loss of water molecules by introducing saturated water vapor during the deposition step, and adsorbing water molecules in the powder in advance, which helps to form a water mist layer, thereby forming a water vapor atmosphere, which can increase the hydroxyl content in the obtained quartz glass.
[0090] In the deposition process of the present invention, the silicon source has an inlet flow rate of 20-60 g / min and an inlet flow rate of 1.0-2.0 mm / s. Within the above inlet flow rate and inlet flow rate ranges, the silicon source can be promoted to react better with hydrogen and oxygen, avoiding burner blockage caused by insufficient reaction, and can also promote the size of the deposited powder particles to be appropriate, avoiding the problem of powder particles agglomerating and causing problems that are not conducive to the absorption of water molecules.
[0091] In the deposition process of the present invention, saturated water vapor is introduced into the deposition chamber 3 through the water mist torch 5; the angle formed by the axis of the water mist torch 5 and the ground plane is α, and α is 30°-55°. The present invention limits the angle range of the angle α formed by the water mist torch 5 and the ground plane, which is conducive to limiting the range of the flame covering the powder rod 2 and avoiding the cracking of the powder; if the angle is too large or too small, it is easy to cause cracking.
[0092] In the deposition process of the present invention, the mixed gas is introduced into the deposition chamber 3 through the deposition torch 7; the distance from the nozzle of the deposition torch 7 to the intersection of the axis of the deposition torch 7 and the axis of the quartz target rod 1 is L, in m, the flow rate of the silicon source is v, in mm / s, and the numerical relationship between L and v satisfies L=(0.05-0.3)×v; preferably, L is 0.05-0.6 m. The present invention defines the numerical relationship between L and v, which can promote the good matching effect between the flow rate of the silicon source introduced and the distance between the quartz target rod 1 and the deposition torch 7, thereby preventing the SiO2 generated by the silicon source and hydrogen and oxygen from causing a serious agglomeration reaction due to excessive temperature, further ensuring that the SiO2 powder is evenly dispersed on the quartz target rod 1 to form a powder layer, and at the same time promoting the size of the powder particles in the powder layer to be within 140 nm, with a large specific surface area to adsorb hydroxyl groups and water molecules. It has been verified by experiments that the quartz glass prepared when L is 0.05-0.6 m has a uniform hydroxyl distribution and a high hydroxyl content.
[0093] In step 2 of the present invention, quartz glass can be obtained by sequentially performing a first sintering and a second sintering on the powder rod 2 .
[0094] During the first sintering process, a mixed atmosphere of saturated water vapor and oxygen is introduced, and a high humidity environment is created by the saturated water vapor. Combined with the high temperature and high pressure environment, the saturated water vapor can be made to penetrate into the inside of the powder rod 2. At the same time, since the saturated water vapor and oxygen are introduced from the bottom and discharged from the top of the powder rod 2, the water molecules and oxygen molecules of the powder rod 2 can be evenly dispersed in the powder layer in the longitudinal direction. In addition, the first sintering can also reduce the influence of high temperature radiation in the second sintering on the hydroxyl content of the powder rod 2 itself, ensuring that the hydroxyl groups of the powder rod 2 are evenly distributed from the inside to the outside.
[0095] During the second sintering process, a mixed atmosphere of saturated water vapor, oxygen and helium is introduced. The high temperature conditions of the second sintering are used to force oxygen atoms to fill the network structure to form peroxide bonds (Si-OO-Si) defects, and can also cause high-temperature decomposition of water molecules to form alcohol structures (Si-OH), further increasing the hydroxyl content in the quartz glass. At the same time, due to the existence of the first sintering, the dehydration and dehydroxylation caused by high-temperature radiation can be reduced by controlling the flow rate of saturated water vapor introduced during the second sintering process. Among them, oxygen is the carrier gas of saturated water vapor; helium, as an inert gas, can be used for heat transfer, causing the inside and outside of the powder rod to be heated and vitrified simultaneously, not just the outer layer.
[0096] In the sintering process of the present invention, the second sintering can be divided into a heating stage and a constant temperature stage. The flow rate of saturated water vapor in the first sintering is Q1, in L / min; the flow rate of saturated water vapor in the second sintering is Q2, in L / min, and the speed increase of the flow rate is k2, in L / min. min; the heating time in the second sintering stage is t, unit is min; when Q2, Q1, k2 and The numerical relationship of t satisfies Q2=Q1+k2× At t, the flow rate of the saturated water vapor of the second sintering has a good matching effect with the heating process, which can ensure that the saturated water vapor and oxygen molecules can effectively penetrate the powder rod 2 in the radial direction. This is because the heating will cause the powder rod 2 to shrink, which will lead to the radial infiltration of water molecules. At this time, the flow rate of the saturated water vapor is adjusted accordingly to avoid the water molecules that have not yet penetrated into the interior of the powder rod 2 due to insufficient flow rate. The outer layer of the powder rod 2 has been densified, thereby blocking the water molecules from continuing to penetrate inward. At the same time, under this condition, the diffusion power of saturated water vapor and oxygen is slightly higher than the void contraction power of the powder in the powder layer, ensuring that water molecules penetrate inward, thereby avoiding the uneven internal and external diffusion of powder particles caused by the high temperature difference between the inside and outside. It can be understood that since the powder rod 2 is also evenly distributed with saturated water vapor in the axial direction, the distribution of its hydroxyl content in the axial direction is also uniform. Preferably, when Q1 is 10-80 L / min, the hydroxyl uniformity and hydroxyl content of the quartz glass can be further improved. In the present invention, k2 is preferably 2.4-7.5 L / min min, t is the time required for the temperature of the first sintering stage to rise to the temperature of the second sintering constant temperature stage.
[0097] In one embodiment of the present invention, the flow rate Q1 of saturated water vapor in the first sintering is 50 L / min, the first sintering temperature is 800°C, the temperature of the second sintering constant temperature stage is 1500°C, and the heating time is t is 350 min, oxygen is used as carrier gas at a flow rate of Q2, 3 L / min min flow rate k2 into 100 ° C saturated steam, where the flow rate Q2 and flow rate Q1, flow rate k2, heating time t satisfies Q2=Q1+k2× The numerical relationship of t, and the unit of flow rate Q2 is L / min. When the temperature rises to 1500℃, the corresponding flow rate Q2 is 1100 L / min.
[0098] The present invention does not limit the sintering devices used for the first sintering and the second sintering. In one embodiment of the present invention, the first sintering and the second sintering are performed in the same device, and the first sintering is achieved by fixing the deposited powder rod 2 through the hanging rod fixing end 13, so that the powder rod 2 is placed in the upper furnace body 17 of the device. When the first sintering is completed, the partition plate 18 between the upper furnace body 17 and the sintering furnace 21 of the device can be opened, and the powder rod 2 after the first sintering can be moved into the sintering furnace 21, and the partition plate 18 is closed again and the central hanging rod is retained to pass through the partition plate 18 to start the second sintering. It is understandable that separate devices can also be used to perform the first sintering and the second sintering respectively.
[0099] The preparation method provided by the present invention adopts an axial vapor deposition method and a secondary sintering method, and can obtain quartz glass with a transparent appearance, greatly improve the production efficiency while ensuring the hydroxyl content, and facilitate subsequent mass production.
[0100] In the above technical solution, the deposition conditions include: a pressure of 0.5-3 Pa. Experimental verification shows that maintaining the pressure in the deposition chamber 3 at 0.5-3 Pa in step 1 can enable water vapor to make up for the water loss in high-temperature deposition.
[0101] In the above technical solution, the conditions of the first sintering include: temperature of 400-800°C, pressure of 100-300 pa, and time of 24-72 hours. The temperature, pressure and time of the first sintering are limited to the above ranges, which can ensure gas exchange and pressure adjustment during the first sintering, thereby increasing the ambient humidity during the first sintering, and with the temperature and time control, it can further promote the absorption of saturated water vapor by the powder rod 2 and the synthesis of hydroxyl groups.
[0102] In the above technical solution, the conditions of the second sintering include: the temperature of the constant temperature stage is 1250-1500°C, the pressure is 3-5 pa, and the time is 4-8 hours. The temperature, pressure and time of the constant temperature stage in the second sintering are limited to meet the above ranges, which can ensure that the obtained quartz glass has a transparent appearance and uniformly distributed hydroxyl groups. In particular, maintaining the pressure of the second sintering at 3-5 pa in step 2 can promote better diffusion of water vapor into the interior of the powder rod 2, further promoting the increase of the hydroxyl content and the uniform distribution of hydroxyl groups.
[0103] It can be understood that when any one of the deposition conditions, the first sintering conditions, and the second sintering conditions meets the above range, the hydroxyl content can be increased and the hydroxyl distribution can be uniform; when all are met, the hydroxyl content can be better promoted and the hydroxyl distribution can be uniform.
[0104] In a specific embodiment, in step 1, the flow rate of saturated water vapor is 10-50 L / min; in step 1, the flow rate of hydrogen is 60-110 L / min; in step 1, the flow rate of oxygen is 30-120 L / min; in step 1, the flow rate of argon is 10-15 L / min; in step 2, the flow rate of helium in the second sintering is 10-50 L / min. In the present invention, by limiting the flow rate of saturated water vapor, hydrogen, oxygen or argon in step 1, the amount of saturated water vapor, hydrogen, oxygen and argon can be controlled to be appropriate, so as to better obtain quartz glass with uniform hydroxyl distribution and high hydroxyl content. In the present invention, by limiting the flow rate of helium, the role of helium in heat transfer can be further improved, thereby promoting the synchronous heating and vitrification of the inside and outside of the powder rod.
[0105] It can be understood that when the flow rate of any one of saturated water vapor, hydrogen, oxygen, argon and helium is regulated to meet the above range, the hydroxyl content of the quartz glass can be increased and the hydroxyl distribution can be uniform; when all of them are met, the hydroxyl content of the quartz glass can be better increased and the hydroxyl distribution can be uniform.
[0106] In the technical solution of the present invention, in step 2, the speed increase of the flow rate of saturated water vapor in the second sintering is k2, in units of L / min. min; the heating rate in the second sintering is k1, in °C / min; the numerical relationship between k2 and k1 satisfies k2=(1.2-1.5)×k1; preferably, k1 is 2-5 °C / min, and k2 is 2.4-7.5 L / min The numerical relationship between k2 and k1 is limited to satisfy the above relationship, which can further promote a good matching effect between the inflow rate of saturated water vapor and the heating rate of the second sintering, thereby ensuring that the saturated water vapor and oxygen molecules effectively penetrate the powder rod 2 in the radial direction.
[0107] In the above technical solution, in step 1, the horizontal angle between the water mist torch and the deposition torch is θ, and θ is 30°-150°; preferably, θ is 30°-120°.
[0108] The present invention defines the horizontal angle θ between the water mist burner 5 and the deposition burner 7 in step 1 as 30°-150°, and can control the SiO2 powder particles sprayed by the deposition burner 7 to pass through the water mist layer formed by the water mist burner 5 at a suitable angle, and utilize the characteristic of the powder particles adsorbing water to cause the powder particles to wrap and adsorb water molecules, thereby further increasing the hydroxyl content in the obtained quartz glass. It has been verified by experiments that when θ is 30°-120°, the hydroxyl content of the obtained quartz glass is higher.
[0109] In the above technical scheme, in step 1, the quartz target rod is deposited by the axial vapor deposition method, and the rotation speed of the quartz target rod is set to 5-30 r / min; the rotation speed matches the preparation method of the present invention, which helps to deposit the SiO2 powder sprayed by the blowtorch 7 and the saturated water vapor sprayed by the water mist blowtorch 5 to be uniformly attached to the surface of the quartz target rod 1, so as to better generate the target quartz glass. In addition, in step 1, the quartz target rod is deposited by the axial vapor deposition method, and the rod lifting speed of the quartz target rod is set to 30-100 mm / h. The rod lifting speed matches the preparation method of the present invention, which helps to make the deposition result more uniform and better generate the target quartz glass. It can be understood that when any one of the rotation speed and the rod lifting speed is adjusted to meet the above range, the generation of the target quartz glass can be promoted; when all are satisfied, the generation of the target quartz glass can be better promoted.
[0110] In the above technical solution, in step 1, the diameter of the powder particles on the powder rod is 40-140 nm. Within this range, the powder particles are of appropriate size and have an appropriate specific surface area, thereby avoiding the problem of powder particle agglomeration causing problems in absorbing water molecules.
[0111] The third aspect of the present invention provides an application of the above-mentioned quartz glass or the quartz glass prepared by the above-mentioned preparation method in the fields of special experimental equipment, aerospace, ultraviolet energy transmission, and nuclear power radiation resistance.
[0112] Special experimental equipment requires high precision and high reliability, and uniform hydroxyl distribution can ensure the consistency of optical and mechanical properties of materials and enhance the chemical stability of materials, thereby reducing experimental errors. Aerospace equipment is often exposed to extreme temperature environments. Uniform hydroxyl distribution helps quartz glass maintain stable thermal expansion characteristics when the temperature changes, reducing the risk of thermal stress and material failure; at the same time, uniform hydroxyl distribution can improve the overall mechanical strength and durability of materials in high-stress environments, ensuring safety and reliability. The field of ultraviolet energy transmission requires materials to have high transmittance, and uniform hydroxyl distribution reduces the unevenness of light absorption and improves the transmission efficiency of ultraviolet light; at the same time, in ultraviolet optical systems, uniform hydroxyl distribution can ensure the consistency of optical properties, thereby reducing optical distortion and loss. In a radiation environment, uniform hydroxyl distribution can improve the radiation resistance of quartz glass and reduce material degradation caused by radiation; it also helps to extend the service life of the material in a radiation environment and ensure its long-term stability under harsh conditions. The quartz glass of the present invention has a hydroxyl content difference of ≤100 ppm in the axial direction and a hydroxyl content difference of ≤100 ppm in the radial direction, and has uniform hydroxyl distribution in both the axial and radial directions, and thus can be applied to the above-mentioned fields.
[0113] The technical solution of the present application will be further explained below in conjunction with specific examples. The experimental methods in the following examples that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The reagents used are commercially available or available from public channels unless otherwise specified.
[0114] Embodiment 1:
[0115] (1) Deposition:
[0116] use Figure 1 The axial vapor deposition (VAD) machine shown in the figure is used for deposition, wherein the quartz target rod 1 is fixed at the inside of the deposition chamber 3 through the fixed end 4, the water mist torch 5 and the deposition torch 7 are located at the lower part of the side of the deposition chamber 3, the first exhaust pipe 6 is located at the upper part of the side of the deposition chamber 3, and a pressure gauge 12 is also provided on the side of the deposition chamber to monitor the internal pressure of the deposition chamber 3. The raw material pipeline port 8, the argon channel port 9, the hydrogen channel port 10, and the oxygen channel port 11 are connected to the deposition torch 7. After deposition, a layer of powder particles will be attached to the surface of the quartz target rod 1 to form a powder rod 2. Figure 1 As shown, the distance L from the nozzle of the deposition torch 7 to the intersection of the axial direction of the deposition torch 7 and the axial direction of the quartz target rod 1 is 0.1 m; Figure 2 As shown, the angle α formed by the axis of the water mist torch 5 and the ground plane is 55°; Figure 3 As shown, the horizontal angle θ between the water mist torch 5 and the deposition torch 7 is 30°.
[0117] Click the rod body to rotate and set the rotation speed of the quartz target rod 1 to 5 r / min. Open the first exhaust pipe 6 and the water mist torch 5, use oxygen as the carrier gas to pass 100°C saturated water vapor from the water mist torch 5 at a flow rate of 50 L / min, and form a water vapor atmosphere in the deposition chamber 3 with a pressure of 3 pa. Then, the raw material SiCl4 is introduced from the raw material pipeline port 8 at a flow rate of 60 g / min and a flow rate v of 2.0 mm / s, H2 is introduced from the hydrogen channel port 10 at a flow rate of 60 L / min, O2 is introduced from the oxygen channel port 11 at a flow rate of 120 L / min, and Ar is introduced from the argon channel port 9 at a flow rate of 10 L / min, wherein the aforementioned distance L and the flow rate v satisfy the numerical relationship of L=(0.05-0.3)×v. The ignition operation is performed to burn at the lamp mouth of the deposition torch 7 to form a high-temperature flame reaction to spray the generated silicon dioxide onto the quartz target rod 1, and the rod lifting speed is constant at 30 mm / h until the deposition length reaches 1200 mm, and the deposition is completed to obtain the powder rod 2. The diameter of the powder particles on the powder rod 2 is 40-65 nm when detected by scanning electron microscopy (SEM).
[0118] (2) Sintering:
[0119] use Figure 4 The sintering furnace equipment shown in the figure is used for deposition, wherein the sintering furnace equipment is divided into an upper furnace body 17 and a sintering furnace 21, the upper furnace body 17 is located at the upper part of the sintering furnace 21 and is separated by a partition plate 18; the powder rod 2 is fixed to the inside of the upper furnace body 17 by a hanging rod fixed end 13 and is sealed by a sealing ring 14 at the top of the upper furnace body 17, the first air supply pipe 16 is located at the lower part of the side of the upper furnace body 17, and the second exhaust pipe 15 is located at the upper part of the side of the upper furnace body 17; after opening the partition plate 18, the powder rod 2 can be transferred from the upper furnace body 17 to the sintering furnace 21 for sintering, and the partition plate 18 is closed, and only the center hanging rod is retained to pass through the partition plate 18 before sintering can be started. At this time, the powder rod 2 is suspended in the inside of the sintering furnace 21, the inlet of the second air supply pipe 22 is located at the lower part of the side of the sintering furnace 21, and the outlet is located at the bottom surface of the sintering furnace 21, the third exhaust pipe 19 is located at the upper part of the side of the sintering furnace 21, and the graphite resistor 20 is located on the inner wall of the sintering furnace 21.
[0120] The powder rod 2 obtained in step (1) is fixed by the fixed end 13 of the suspension rod, lowered into the upper furnace body 17, and the sealing ring 14 is installed and fixed. The second exhaust pipe 15 and the first air supply pipe 16 are opened, and saturated water vapor at 100°C is introduced from the first air supply pipe 16 at a flow rate Q1 of 50 L / min using oxygen as a carrier gas. At this time, the temperature in the upper furnace body 17 is 800°C and the pressure is 300 Pa. The powder rod 2 is kept pressurized and suspended for 72 hours.
[0121] Then, exhaust gas through the second exhaust pipe 15 to adjust the pressure back to 1 pa, open the partition plate 18, transfer the powder rod 2 from the upper furnace body 17 to the sintering furnace 21 for sintering, close the partition plate 18 again, and keep the central suspension rod through. Open the third exhaust pipe 19 and the second air supply pipe 22, and introduce He from the second air supply pipe 22 at a flow rate of 40 L / min, and heat it from 800°C to 1500°C through the graphite resistor 20 at a heating rate k1 of 2°C / min. The heating time is At the same time, oxygen is used as a carrier gas from the second gas supply pipe 22 at a flow rate of Q2, 3 L / min min flow rate k2 into 100 ° C saturated steam, where the flow rate Q2 and flow rate Q1, flow rate k2, heating time t satisfies Q2=Q1+k2× t, and the unit of flow Q2 is L / min. When the temperature rises to 1500℃, the corresponding flow Q2 is 1100 L / min; the flow rate increase k2 and the heating rate k1 satisfy the numerical relationship of k2=(1.2-1.5)×k1. After the temperature reaches 1500℃, maintain constant temperature (1500℃), constant pressure (5pa), and constant flow (He maintains a flow rate of 40 L / min, and saturated water vapor at 100℃ maintains a flow rate of 1100 L / min) for vitrification for 4 hours to obtain a quartz glass rod. Among them, the temperature-time curve of the sintering step is as shown in Figure 5 As shown, the relationship between the saturated water vapor flow-time curve and the sintering temperature-time curve of the sintering step is shown in Figure 6 shown.
[0122] (3) Testing:
[0123] The hydroxyl content of the obtained quartz glass rod was tested by Fourier infrared tester. A point was set every 100 mm along the axial direction of the quartz glass from the bottom to the top, and three points were evenly tested from this point to the edge in the radial direction, which were set as radial 1, radial 2 and radial 3. Figure 7 .
[0124] according to Figure 7 It can be seen from the results that the hydroxyl content of the quartz glass rod of this embodiment changes slightly with the change of the axial point position, indicating that the fluctuation range of the hydroxyl content in the axial direction is small; at the same time, the radial hydroxyl content of the quartz glass rod changes slightly when the quartz glass rod is at the same axial point position, indicating that the fluctuation range of the hydroxyl content in the radial direction is small; after testing, the hydroxyl content of the quartz glass rod obtained in this embodiment is 1200 ppm±15 ppm in both the axial and radial directions, and has a high hydroxyl content and good uniformity.
[0125] Embodiment 2:
[0126] (1) Deposition:
[0127] use Figure 1 The axial vapor deposition (VAD) machine shown in the figure is used for deposition. Its structure can refer to Example 1, except that the distance L from the nozzle of the deposition torch 7 to the intersection of the axial direction of the deposition torch 7 and the axial direction of the quartz target rod 1 is 0.15 m; the angle α formed by the axis of the water mist torch 5 and the ground plane is 45°; the horizontal angle θ between the water mist torch 5 and the deposition torch 7 is 75°.
[0128] Click the rod body to rotate and set the rotation speed of the quartz target rod 1 to 15 r / min. Open the first exhaust pipe 6 and the water mist torch 5, use oxygen as the carrier gas to pass 100°C saturated water vapor from the water mist torch 5 at a flow rate of 30 L / min, and form a water vapor atmosphere in the deposition chamber 3 with a pressure of 2 pa. Then, the raw material SiCl4 is introduced from the raw material pipeline port 8 at a flow rate of 45 g / min and a flow rate v of 1.5 mm / s, H2 is introduced from the hydrogen channel port 10 at a flow rate of 105 L / min, O2 is introduced from the oxygen channel port 11 at a flow rate of 60 L / min, and Ar is introduced from the argon channel port 9 at a flow rate of 12.5 L / min, wherein the aforementioned distance L and the flow rate v satisfy the numerical relationship of L=(0.05-0.3)×v. The ignition operation is performed to burn at the lamp mouth of the deposition torch 7 to form a high-temperature flame reaction to spray the generated silicon dioxide onto the quartz target rod 1, and the rod lifting speed is constant at 65 mm / h until the deposition length reaches 1200 mm, and the deposition is completed to obtain the powder rod 2. The diameter of the powder particles on the powder rod 2 is 75-105 nm when detected by SEM.
[0129] (2) Sintering:
[0130] use Figure 4 The sintering furnace equipment shown in the figure is used for sintering, and its structure can refer to Example 1. The powder rod 2 obtained in step (1) is fixed by the fixed end 13 of the suspension rod, lowered into the upper furnace body 17, and the sealing ring 14 is installed and fixed. The second exhaust pipe 15 and the first air supply pipe 16 are opened, and saturated water vapor at 100°C is introduced from the first air supply pipe 16 at a flow rate Q1 of 35 L / min with oxygen as the carrier gas. At this time, the temperature in the upper furnace body 17 is 600°C and the pressure is 200 Pa. The powder rod 2 is kept pressurized and suspended for 36 hours.
[0131] Subsequently, exhaust gas through the second exhaust pipe 15 to adjust the pressure back to 1 pa, open the partition plate 18, transfer the powder rod 2 from the upper furnace body 17 to the sintering furnace 21 for sintering, close the partition plate 18 again, and keep the central suspension rod through. Open the third exhaust pipe 19 and the second air supply pipe 22, and introduce He from the second air supply pipe 22 at a flow rate of 25 L / min, and heat it from 600°C to 1350°C through the graphite resistor 20 at a heating rate k1 of 3.5°C / min. The heating time is At the same time, oxygen is used as a carrier gas from the second gas supply pipe 22 at a flow rate of Q2, 4.5 L / min min flow rate k2 into 100 ° C saturated steam, where the flow rate Q2 and flow rate Q1, flow rate k2, heating time t satisfies Q2=Q1+k2× t, and the unit of flow Q2 is L / min. When the temperature rises to 1350℃, the corresponding flow Q2 is 998 L / min; the flow rate increase k2 and the heating rate k1 satisfy the numerical relationship of k2=(1.2-1.5)×k1. After the temperature reaches 1350℃, the constant temperature (1350℃), constant pressure (4 pa), and constant flow (He maintains a flow of 25 L / min, and saturated water vapor at 100℃ maintains a flow of 998 L / min) are maintained for vitrification for 6 hours to obtain a quartz glass rod.
[0132] (3) Testing:
[0133] The hydroxyl content of the obtained quartz glass rod was tested by Fourier infrared tester. A point was set every 100 mm along the axial direction of the quartz glass from the bottom to the top, and three points were evenly tested from this point to the edge in the radial direction, which were set as radial 1, radial 2 and radial 3. Figure 8 .
[0134] according to Figure 8 It can be seen from the results that the hydroxyl content of the quartz glass rod of this embodiment changes slightly with the change of the axial point position, indicating that the fluctuation range of the hydroxyl content in the axial direction is small; at the same time, the radial hydroxyl content of the quartz glass rod changes slightly when the quartz glass rod is at the same axial point position, indicating that the fluctuation range of the hydroxyl content in the radial direction is small; after testing, the hydroxyl content of the quartz glass rod obtained in this embodiment is 1150 ppm±20 ppm in both the axial and radial directions, and has a high hydroxyl content and good uniformity.
[0135] Embodiment 3:
[0136] (1) Deposition:
[0137] use Figure 1The axial vapor deposition (VAD) machine shown in the figure is used for deposition. Its structure can refer to Example 1, except that the distance L from the nozzle of the deposition torch 7 to the intersection of the axial direction of the deposition torch 7 and the axial direction of the quartz target rod 1 is 0.2 m; the angle α formed by the axis of the water mist torch 5 and the ground plane is 35°; the horizontal angle θ between the water mist torch 5 and the deposition torch 7 is 120°.
[0138] Click the rod body to rotate and set the rotation speed of the quartz target rod 1 to 25 r / min. Open the first exhaust pipe 6 and the water mist torch 5, use oxygen as the carrier gas to pass 100°C saturated water vapor from the water mist torch 5 at a flow rate of 10 L / min, and form a water vapor atmosphere in the deposition chamber 3 with a pressure of 1 pa. Then, the raw material SiCl4 is introduced from the raw material pipeline port 8 at a flow rate of 30 g / min and a flow rate v of 1.0 mm / s, H2 is introduced from the hydrogen channel port 10 at a flow rate of 90 L / min, O2 is introduced from the oxygen channel port 11 at a flow rate of 30 L / min, and Ar is introduced from the argon channel port 9 at a flow rate of 10 L / min, wherein the aforementioned distance L and the flow rate v satisfy the numerical relationship of L=(0.05-0.3)×v. The ignition operation is performed to burn at the lamp mouth of the deposition torch 7 to form a high-temperature flame reaction to spray the generated silicon dioxide onto the quartz target rod 1, and the rod lifting speed is kept at 100 mm / h until the deposition length reaches 1200 mm, and the deposition is completed to obtain the powder rod 2. The diameter of the powder particles on the powder rod 2 is 95-120 nm as detected by SEM.
[0139] (2) Sintering:
[0140] use Figure 4 The sintering furnace equipment shown in the figure is used for sintering, and its structure can refer to Example 1. The powder rod 2 obtained in step (1) is fixed by the fixed end 13 of the suspension rod, lowered into the upper furnace body 17, and the sealing ring 14 is installed and fixed. The second exhaust pipe 15 and the first air supply pipe 16 are opened, and saturated water vapor at 100°C is introduced from the first air supply pipe 16 at a flow rate Q1 of 10 L / min with oxygen as the carrier gas. At this time, the temperature in the upper furnace body 17 is 400°C and the pressure is 100 Pa. The powder rod 2 is kept pressurized and suspended for 24 hours.
[0141] Subsequently, exhaust gas through the second exhaust pipe 15 to adjust the pressure back to 1 pa, open the partition plate 18, transfer the powder rod 2 from the upper furnace body 17 to the sintering furnace 21 for sintering, close the partition plate 18 again, and keep the central suspension rod through. Open the third exhaust pipe 19 and the second air supply pipe 22, and introduce He from the second air supply pipe 22 at a flow rate of 10 L / min, and heat it from 400°C to 1250°C through the graphite resistor 20 at a heating rate k1 of 5°C / min. The heating time is 200 °C. At the same time, oxygen is used as a carrier gas from the second gas supply pipe 22 at a flow rate of Q2,6 L / min min flow rate k2 into 100 ° C saturated steam, where the flow rate Q2 and flow rate Q1, flow rate k2, heating time t satisfies Q2=Q1+k2× t, and the unit of flow Q2 is L / min. When the temperature rises to 1250℃, the corresponding flow Q2 is 1030 L / min; the flow rate increase k2 and the heating rate k1 satisfy the numerical relationship of k2=(1.2-1.5)×k1. After the temperature reaches 1250℃, the constant temperature (1250℃), constant pressure (3pa), and constant flow (He maintains a flow of 10 L / min, and saturated water vapor at 100℃ maintains a flow of 1030 L / min) are maintained for vitrification for 8 hours to obtain a quartz glass rod.
[0142] (3) Testing:
[0143] The hydroxyl content of the obtained quartz glass rod was tested by a Fourier infrared tester. A point was set every 100 mm along the axial direction of the quartz glass from the bottom to the top, and three points were evenly tested from this point to the edge in the radial direction, which were set as radial 1, radial 2 and radial 3 respectively.
[0144] After testing, it is found that the hydroxyl content of the quartz glass rod of this embodiment changes slightly with the change of the axial point position, indicating that the fluctuation range of the hydroxyl content in the axial direction is small; at the same axial point position, the radial hydroxyl content of the quartz glass rod changes slightly, indicating that the fluctuation range of the hydroxyl content in the radial direction is small; the hydroxyl content of the quartz glass rod obtained in this embodiment is 1120 ppm±25 ppm in both the axial and radial directions, and has a high hydroxyl content and good uniformity.
[0145] Embodiment 4:
[0146] 1) Deposition:
[0147] use Figure 1 The axial vapor deposition (VAD) machine shown in the figure is used for deposition. Its structure can refer to Example 1, except that the distance L from the nozzle of the deposition torch 7 to the intersection of the axial direction of the deposition torch 7 and the axial direction of the quartz target rod 1 is 0.3 m; the angle α formed by the axis of the water mist torch 5 and the ground plane is 35°; the horizontal angle θ between the water mist torch 5 and the deposition torch 7 is 60°.
[0148] Click the rod body to rotate and set the rotation speed of the quartz target rod 1 to 25 r / min. Open the first exhaust pipe 6 and the water mist torch 5, use oxygen as the carrier gas to pass 100°C saturated water vapor from the water mist torch 5 at a flow rate of 50 L / min, and form a water vapor atmosphere in the deposition chamber 3 with a pressure of 3 pa. Then, the raw material SiCl4 is introduced from the raw material pipeline port 8 at a flow rate of 60 g / min and a flow rate v of 1.5 mm / s, H2 is introduced from the hydrogen channel port 10 at a flow rate of 90 L / min, O2 is introduced from the oxygen channel port 11 at a flow rate of 120 L / min, and Ar is introduced from the argon channel port 9 at a flow rate of 10 L / min, wherein the aforementioned distance L and the flow rate v satisfy the numerical relationship of L=(0.05-0.3)×v. The ignition operation is performed to make the nozzle of the deposition torch 7 burn to form a high-temperature flame reaction to spray the generated silicon dioxide onto the quartz target rod 1, and the rod lifting speed is constant at 80 mm / h until the deposition length reaches 1200 mm, and the deposition is completed to obtain the powder rod 2. The diameter of the powder particles on the powder rod 2 is 55-85 nm as detected by SEM.
[0149] (2) Sintering:
[0150] use Figure 4 The sintering furnace equipment shown in the figure is used for sintering, and its structure can refer to Example 1. The powder rod 2 obtained in step (1) is fixed by the fixed end 13 of the suspension rod, lowered into the upper furnace body 17, and the sealing ring 14 is installed and fixed. The second exhaust pipe 15 and the first air supply pipe 16 are opened, and saturated water vapor at 100°C is introduced from the first air supply pipe 16 at a flow rate Q1 of 50 L / min with oxygen as the carrier gas. At this time, the temperature in the upper furnace body 17 is 800°C and the pressure is 300 Pa. The powder rod 2 is kept pressurized and suspended for 36 hours.
[0151] Subsequently, exhaust gas through the second exhaust pipe 15 to adjust the pressure back to 1 pa, open the partition plate 18, transfer the powder rod 2 from the upper furnace body 17 to the sintering furnace 21 for sintering, close the partition plate 18 again, and keep the central suspension rod through. Open the third exhaust pipe 19 and the second air supply pipe 22, and introduce He from the second air supply pipe 22 at a flow rate of 40 L / min, and heat from 800°C to 1500°C through the graphite resistor 20 at a heating rate k1 of 5°C / min. The heating time is At the same time, oxygen is used as a carrier gas from the second gas supply pipe 22 at a flow rate of Q2, 6.75 L / min min flow rate k2 into 100 ° C saturated steam, where the flow rate Q2 and flow rate Q1, flow rate k2, heating time t satisfies Q2=Q1+k2× t, and the unit of flow rate Q2 is L / min. When the temperature rises to 1500℃, the corresponding flow rate Q2 is 995 L / min; the flow rate increase rate k2 and the heating rate k1 satisfy the numerical relationship of k2=(1.2-1.5)×k1. After the temperature reaches 1500℃, the constant temperature (1500℃), constant pressure (5 pa), and constant flow rate (He maintains a flow rate of 40 L / min, and saturated water vapor at 100℃ maintains a flow rate of 995 L / min) are maintained for vitrification for 4 hours to obtain a quartz glass rod.
[0152] (3) Testing:
[0153] The hydroxyl content of the obtained quartz glass rod was tested by Fourier infrared tester. A point was set every 100 mm along the axial direction of the quartz glass from the bottom to the top, and three points were evenly tested from this point to the edge in the radial direction, which were set as radial 1, radial 2 and radial 3. Fig. 9 .
[0154] according to Fig. 9 It can be seen from the results that the hydroxyl content of the quartz glass rod of this embodiment changes slightly with the change of the axial point position, indicating that the fluctuation range of the hydroxyl content in the axial direction is small; at the same time, the radial hydroxyl content of the quartz glass rod changes slightly when the quartz glass rod is at the same axial point position, indicating that the fluctuation range of the hydroxyl content in the radial direction is small; after testing, the hydroxyl content of the quartz glass rod obtained in this embodiment is 990 ppm±15 ppm in both the axial and radial directions, and has a high hydroxyl content and good uniformity.
[0155] Embodiment 5:
[0156] This embodiment can refer to Embodiment 4, except that in step (1) of this embodiment, the raw material SiCl4 is introduced from the raw material pipeline port 8 at a flow rate of 20 g / min and a flow velocity v of 1.5 mm / s, and the powder particle diameter on the powder rod 2 detected by SEM is 115-140 nm.
[0157] The hydroxyl content of the quartz glass rod obtained in this embodiment was tested using a Fourier infrared tester in reference example 4. The hydroxyl content of the quartz glass rod fluctuated slightly in the axial direction and in the radial direction. After testing, the hydroxyl content of the quartz glass rod obtained in this embodiment was 950 ppm±25 ppm in both the axial and radial directions, and had a high hydroxyl content and good uniformity.
[0158] Embodiment 6:
[0159] This embodiment can refer to Embodiment 4, except that in step (1) of the present embodiment, the distance L from the nozzle of the deposition torch 7 to the intersection of the axial direction of the deposition torch 7 and the axial direction of the quartz target rod 1 is 0.45 m, satisfying the relationship L = (0.05-0.3) × v.
[0160] The hydroxyl content of the quartz glass rod obtained in this embodiment was tested using a Fourier infrared tester in reference example 4. The hydroxyl content of the quartz glass rod fluctuated slightly in the axial direction and in the radial direction. After testing, the hydroxyl content of the quartz glass rod obtained in this embodiment was 860 ppm±23 ppm in both the axial and radial directions, and had a high hydroxyl content and good uniformity.
[0161] Embodiment 7:
[0162] This embodiment can refer to Embodiment 4, except that in step (1) of this embodiment, during deposition, the rotation speed of the quartz target rod 1 is set to 30 r / min by clicking the rod body to rotate.
[0163] The hydroxyl content of the quartz glass rod obtained in this embodiment was tested using a Fourier infrared tester in reference example 4. The hydroxyl content of the quartz glass rod fluctuates slightly in the axial direction and in the radial direction. After testing, the hydroxyl content of the quartz glass rod obtained in this embodiment is 800 ppm±22 ppm in both the axial and radial directions, and has a high hydroxyl content and good uniformity.
[0164] Embodiment 8:
[0165] This embodiment can refer to Embodiment 4, except that in step (1) of the deposition in this embodiment, the angle α formed by the axis of the water mist torch 5 and the ground plane is 30°.
[0166] The hydroxyl content of the quartz glass rod obtained in this embodiment was tested using a Fourier infrared tester in reference example 4. The hydroxyl content of the quartz glass rod fluctuated slightly in the axial direction and in the radial direction. After testing, the hydroxyl content of the quartz glass rod obtained in this embodiment was 930 ppm±50 ppm in both the axial and radial directions, and had a high hydroxyl content and good uniformity.
[0167] Embodiment 10:
[0168] This embodiment can refer to the embodiment 4, except that the horizontal angle θ between the water mist torch 5 and the deposition torch 7 in the step (1) of deposition in this embodiment is 150°.
[0169] The hydroxyl content of the quartz glass rod obtained in this embodiment was tested using a Fourier infrared tester with reference to Example 4. After testing, the hydroxyl content of the quartz glass rod obtained in this embodiment was 600 ppm±45 ppm in both the axial and radial directions. It can be found that the uniformity of the quartz glass rod is still good, but the hydroxyl content is significantly reduced. This is because the silicon dioxide produced by the water mist reaction forms an obvious countercurrent phenomenon, resulting in large air flow fluctuations and flame jitters, thereby affecting the generation of hydroxyl groups.
[0170] Embodiment 11:
[0171] This embodiment can refer to Embodiment 4, except that in step (2) of this embodiment, during sintering, saturated water vapor at 100° C. is introduced from the first gas supply pipe 16 at a flow rate Q1 of 80 L / min using oxygen as a carrier gas.
[0172] The hydroxyl content of the quartz glass rod obtained in this embodiment was tested using a Fourier infrared tester in reference example 4. The hydroxyl content of the quartz glass rod fluctuated slightly in the axial direction and in the radial direction. After testing, the hydroxyl content of the quartz glass rod obtained in this embodiment was 980 ppm±45 ppm in both the axial and radial directions, and had a high hydroxyl content and good uniformity.
[0173] Embodiment 12:
[0174] This embodiment can refer to Embodiment 4, except that in step (1) of this embodiment, oxygen is used as a carrier gas during deposition to introduce 100°C saturated water vapor from a water mist blowtorch 5 at a flow rate of 50 L / min, forming a water vapor atmosphere in the deposition chamber 3 with a pressure of 0.5 Pa.
[0175] The hydroxyl content of the quartz glass rod obtained in this embodiment was tested using a Fourier infrared tester in reference example 4. The hydroxyl content of the quartz glass rod fluctuated slightly in the axial direction and in the radial direction. After testing, the hydroxyl content of the quartz glass rod obtained in this embodiment was 820 ppm±22 ppm in both the axial and radial directions.
[0176] Embodiment 13:
[0177] The step (1) deposition of this embodiment can refer to the embodiment 4, except that in the step (2) sintering of this embodiment, "oxygen is used as carrier gas from the second gas supply pipe 22 at a flow rate of Q2.9 L / min" The flow rate k2 of min is used to pass saturated water vapor at 100℃, where the flow rate Q2 is related to the flow rate Q1, flow rate k2, and heating time. t satisfies Q2=Q1+k2× t, and the unit of flow rate Q2 is L / min. When the temperature is raised to 1500°C, the corresponding flow rate Q2 is 1310 L / min; the flow rate k2 and the heating rate k1 no longer satisfy the numerical relationship of k2=(1.2-1.5)×k1. The remaining operations are the same as those in Example 4.
[0178] The quartz glass rod obtained in this embodiment, after sintering, will form an uneven morphology on the surface of the powder rod 2 due to excessive water vapor flow in the heating stage. After vitrification, the surface of the rod is foggy and cannot be used directly. It is necessary to undergo secondary processing such as surface grinding and polishing before the hydroxyl content of the sample can be tested using a Fourier infrared tester. Reference Example 4 uses a Fourier infrared tester to test the hydroxyl content of the quartz glass rod obtained in this embodiment. The quartz glass rod has a small fluctuation range of hydroxyl content in the axial direction and a small fluctuation range of hydroxyl content in the radial direction. After testing, the hydroxyl content of the quartz glass rod obtained in this embodiment is 900 ppm ± 30 ppm in both the axial and radial directions, with high hydroxyl content and good uniformity. However, due to the excessive water vapor flow in the sintering heating stage, the fluctuation range of the hydroxyl content is increased to a certain extent compared with the quartz glass rod obtained in Example 4.
[0179] Comparative Example 1:
[0180] (1) Deposition:
[0181] use Figure 1 The axial vapor deposition (VAD) machine shown in the figure is used for deposition, and its structure can refer to Example 1. The step (1) of this comparative example can refer to Example 1, except that the operation of "turning on the water mist torch 5, using oxygen as a carrier gas to pass 100°C saturated water vapor from the water mist torch 5 at a flow rate of 50 L / min, forming a water vapor atmosphere in the deposition chamber 3 with a pressure of 3 Pa" is not performed, that is, 100°C saturated water vapor is not passed. The diameter of the powder particles on the powder rod 2 detected by SEM is 55-85 nm.
[0182] (2) Sintering:
[0183] use Figure 4 The sintering furnace equipment shown in the figure is used for sintering, and its structure can refer to Example 1. The powder rod 2 obtained in step (1) is fixed by the suspension rod fixed end 13, lowered into the sintering furnace 21, and the sealing ring 14 is installed and fixed. The third exhaust pipe 19 and the second air supply pipe 22 are opened, and He is introduced from the second air supply pipe 22 at a flow rate of 40 L / min. The graphite resistor 20 is controlled to maintain the temperature of the sintering furnace 21 at 1500°C for vitrification for 4 hours to obtain a quartz glass rod.
[0184] (3) Testing:
[0185] The hydroxyl content of the obtained quartz glass rod was tested by Fourier infrared tester. A point was set every 100 mm along the axial direction of the quartz glass from the bottom to the top, and three points were evenly tested from this point to the edge in the radial direction, which were set as radial 1, radial 2 and radial 3. Fig.10 .
[0186] according to Fig.10 The results show that the hydroxyl content of the quartz glass rod in this comparative example changes greatly with the change of the axial point, indicating that the hydroxyl content fluctuates greatly in the axial direction; at the same axial point, the radial hydroxyl content of the quartz glass rod changes greatly, indicating that the hydroxyl content fluctuates greatly in the radial direction; after testing, the hydroxyl content of the quartz glass rod obtained in this comparative example is 480 ppm±190 ppm.
[0187] Comparative Example 2:
[0188] (1) Deposition:
[0189] use Figure 1 The axial vapor deposition (VAD) machine shown in the figure is used for deposition, and its structure can refer to Example 2. The step (1) of this comparative example can refer to Example 2, except that the operation of "turning on the water mist torch 5, using oxygen as carrier gas to pass 100°C saturated water vapor from the water mist torch 5 at a flow rate of 30 L / min, forming a water vapor atmosphere in the deposition chamber 3 with a pressure of 2 Pa" is not performed, that is, 100°C saturated water vapor is not passed. The diameter of the powder particles on the powder rod 2 detected by SEM is 80-110 nm.
[0190] (2) Sintering:
[0191] use Figure 4The sintering furnace equipment shown in the figure is used for sintering, and its structure can refer to Example 2. The powder rod 2 obtained in step (1) is fixed by the fixed end 13 of the suspension rod, and lowered into the upper furnace body 17. The sealing ring 14 is installed and fixed, and the second exhaust pipe 15 and the first air supply pipe 16 are opened. Saturated water vapor at 100°C is introduced from the first air supply pipe 16 at a flow rate Q1 of 35 L / min with oxygen as the carrier gas. At this time, the temperature in the upper furnace body 17 is 650°C and the pressure is 200 Pa. The powder rod 2 is kept pressurized and suspended for 36 hours. After the temperature of the sintering furnace 21 reaches 1350°C through the graphite resistor 20, the pressure is adjusted back to 1 Pa by exhausting through the second exhaust pipe 15, and the partition plate 18 is opened. The powder rod 2 is transferred from the upper furnace body 17 to the sintering furnace 21 for sintering, and the partition plate 18 is closed again, leaving the suspension rod in the center to pass through. The third exhaust pipe 19 and the second gas supply pipe 22 were opened, He was introduced into the second gas supply pipe 22 at a flow rate of 25 L / min, saturated water vapor at 100°C was introduced into the second gas supply pipe 22 at a flow rate of 998 L / min using oxygen as a carrier gas, and constant temperature (1350°C), constant pressure (4 pa), and constant flow rate (He was maintained at a flow rate of 25 L / min, and saturated water vapor at 100°C was maintained at a flow rate of 998 L / min) was maintained for vitrification for 6 hours to obtain a quartz glass rod.
[0192] (3) Testing:
[0193] The hydroxyl content of the obtained quartz glass rod was tested by Fourier infrared tester. A point was set every 100 mm along the axial direction of the quartz glass from the bottom to the top, and three points were evenly tested from this point to the edge in the radial direction, which were set as radial 1, radial 2 and radial 3. Fig.11 .
[0194] In this comparative example, the powder rod 2 did not undergo a stable temperature rise process. At the glass transition temperature, a strong temperature difference was formed inside and outside the powder rod 2 and in the longitudinal direction. The diffusion speed of water mist was different, and the hydroxyl content formed at high temperature was significantly different. Fig.11 The results show that the hydroxyl content of the quartz glass rod in this comparative example changes greatly with the change of the axial point, indicating that the hydroxyl content fluctuates greatly in the axial direction; at the same axial point, the radial hydroxyl content of the quartz glass rod changes greatly, indicating that the hydroxyl content fluctuates greatly in the radial direction; after testing, the hydroxyl content of the quartz glass rod obtained in this comparative example is 530 ppm±180 ppm.
[0195] Comparative Example 3:
[0196] (1) Deposition:
[0197] use Figure 1The axial vapor deposition (VAD) machine shown in the figure is used for deposition, and its structure can refer to Example 3. The difference is that the distance L from the nozzle of the deposition torch 7 to the intersection of the axial direction of the deposition torch 7 and the axial direction of the quartz target rod 1 is 0.4 m; the horizontal angle θ between the water mist torch 5 and the deposition torch 7 is 180°.
[0198] Click the rod body to rotate and set the rotation speed of the quartz target rod 1 to 25 r / min. Open the first exhaust pipe 6 and the water mist torch 5, use oxygen as the carrier gas to pass 100°C saturated water vapor from the water mist torch 5 at a flow rate of 50 L / min, and form a water vapor atmosphere in the deposition chamber 3 with a pressure of 3 pa. Then, the raw material SiCl4 is introduced from the raw material pipeline port 8 at a flow rate of 65 g / min and a flow rate v of 1.5 mm / s, H2 is introduced from the hydrogen channel port 10 at a flow rate of 120 L / min, O2 is introduced from the oxygen channel port 11 at a flow rate of 35 L / min, and Ar is introduced from the argon channel port 9 at a flow rate of 10 L / min, wherein the aforementioned distance L and the flow rate v satisfy the numerical relationship of L=(0.05-0.3)×v. The ignition operation was performed to make the nozzle of the deposition torch 7 burn to form a high-temperature flame reaction to spray the generated silicon dioxide onto the quartz target rod 1, and the rod lifting speed was kept at 100 mm / h until the deposition length reached 1200 mm, and the deposition was completed to obtain the powder rod 2. The diameter of the powder particles on the powder rod 2 was detected by SEM and was 185-260 nm. It was speculated that the excessive amount of H2 and SiCl4 and the insufficient amount of O2 may further aggravate the agglomeration of particles.
[0199] (2) Sintering:
[0200] use Figure 4 The sintering furnace equipment shown in the figure is used for sintering, and its structure can refer to Example 3. The powder rod 2 obtained in step (1) is fixed by the suspension rod fixed end 13, lowered into the upper furnace body 17, the sealing ring 14 is installed and fixed, the second exhaust pipe 15 and the first air supply pipe 16 are opened, and saturated water vapor at 100°C is introduced from the first air supply pipe 16 at a flow rate Q1 of 50 L / min with oxygen as the carrier gas. At this time, the temperature in the upper furnace body 17 is 800°C and the pressure is 300 Pa. The powder rod 2 is kept pressurized and suspended for 72 hours.
[0201] Subsequently, exhaust gas through the second exhaust pipe 15 to adjust the pressure back to 1 pa, open the partition plate 18, transfer the powder rod 2 from the upper furnace body 17 to the sintering furnace 21 for sintering, close the partition plate 18 again, and keep the central suspension rod through. Open the third exhaust pipe 19 and the second air supply pipe 22, and introduce He from the second air supply pipe 22 at a flow rate of 40 L / min, and heat from 800°C to 1500°C through the graphite resistor 20 at a heating rate k1 of 4°C / min. The heating time is At the same time, oxygen is used as a carrier gas from the second gas supply pipe 22 at a flow rate of Q2,4 L / min min flow rate k2 into 100 ° C saturated steam, where the flow rate Q2 and flow rate Q1, flow rate k2, heating time t satisfies Q2=Q1+k2× t, and the unit of flow rate Q2 is L / min. When the temperature rises to 1500℃, the corresponding flow rate Q2 is 750 L / min; the flow rate increase rate k2 and the heating rate k1 no longer satisfy the numerical relationship of k2=(1.2-1.5)×k1. After the temperature reaches 1500℃, the constant temperature (1500℃), constant pressure (3 pa), and constant flow rate (He maintains a flow rate of 40 L / min, and saturated water vapor at 100℃ maintains a flow rate of 750 L / min) are maintained for vitrification for 4 hours to obtain a quartz glass rod.
[0202] (3) Testing:
[0203] The hydroxyl content of the obtained quartz glass rod was tested by Fourier infrared tester. A point was set every 100 mm along the axial direction of the quartz glass from the bottom to the top, and three points were evenly tested from this point to the edge in the radial direction, which were set as radial 1, radial 2 and radial 3. Fig.12 .
[0204] After testing, the quartz glass rod of this comparative example has a large change in hydroxyl content with the change of the axial point, indicating that the hydroxyl content fluctuates greatly in the axial direction; at the same time, the quartz glass rod has a large change in radial hydroxyl content at the same axial point, indicating that the hydroxyl content fluctuates greatly in the radial direction; the hydroxyl content of the quartz glass rod obtained in this comparative example is 385ppm±125ppm.
[0205] Comparative Example 4:
[0206] The sintering step (2) of this comparative example can refer to Example 3, except that the deposition step (1) of this comparative example is different. The specific details of step (1) of this comparative example are as follows:
[0207] (1) Deposition: Use Figure 1 The axial vapor deposition (VAD) machine shown in the figure is used for deposition. Its structure can refer to Example 3, except that the distance L from the nozzle of the deposition torch 7 to the intersection of the axial direction of the deposition torch 7 and the axial direction of the quartz target rod 1 is 0.035 m; the angle α formed by the axis of the water mist torch 5 and the ground plane is 45°; the horizontal angle θ between the water mist torch 5 and the deposition torch 7 is 135°.
[0208] Click the rod body to rotate and set the rotation speed of the quartz target rod 1 to 15 r / min. Open the first exhaust pipe 6 and the water mist torch 5, use oxygen as the carrier gas to pass 100°C saturated water vapor from the water mist torch 5 at a flow rate of 35 L / min, and form a water vapor atmosphere in the deposition chamber 3 with a pressure of 2 pa. Then, the raw material SiCl4 is introduced from the raw material pipeline port 8 at a flow rate of 45 g / min and a flow rate v of 0.8 mm / s, H2 is introduced from the hydrogen channel port 10 at a flow rate of 105 L / min, O2 is introduced from the oxygen channel port 11 at a flow rate of 60 L / min, and Ar is introduced from the argon channel port 9 at a flow rate of 12.5 L / min, wherein the aforementioned distance L and the flow rate v do not satisfy the numerical relationship of L=(0.05-0.3)×v. The ignition operation is performed to make the nozzle of the deposition torch 7 burn to form a high-temperature flame reaction to spray the generated silicon dioxide onto the quartz target rod 1, and the rod lifting speed is constant at 65 mm / h until the deposition length reaches 1200 mm, and the deposition is completed to obtain the powder rod 2. The diameter of the powder particles on the powder rod 2 is 30-115 nm as detected by SEM. In the above deposition process, there are problems such as uneven flame reaction, different particle sizes, and some accumulation at the nozzle of the torch. When repeated for the third time, the torch is blocked and damaged.
[0209] Finally, after sintering in the same step (2) as in Example 3, a quartz glass rod was obtained. Referring to Example 3, the hydroxyl content of the quartz glass rod obtained in this comparative example was tested by a Fourier infrared tester in both the axial and radial directions, and was 650 ppm±45 ppm. Compared with the quartz glass rod obtained in Example 3, the hydroxyl content was significantly reduced, and the fluctuation range of the hydroxyl content was also increased to a certain extent. In addition, after depositing 3 rods, the blowtorch of this comparative example was blocked and damaged, and could not be used in actual production.
[0210] Comparative Example 5:
[0211] This comparative example can refer to Example 4, except that in step (2) of this comparative example, the flow rate Q2 during sintering is always maintained at 600 L / min.
[0212] The hydroxyl content of the quartz glass rod obtained in this embodiment was tested using a Fourier infrared tester in reference to Example 4. The hydroxyl content of the quartz glass rod fluctuated slightly in the axial direction and fluctuated greatly in the radial direction. After testing, the hydroxyl content of the quartz glass rod obtained in this embodiment was 900 ppm±(30-50) ppm in the axial direction and 900 ppm±(40-100) ppm in the radial direction.
[0213] Comparative Example 6:
[0214] This comparative example can refer to Example 4, except that in step (1) of this comparative example, the raw material SiCl4 is introduced from the raw material pipeline port 8 at a flow rate of 70 g / min and a flow velocity v of 1.5 mm / s. After depositing three quartz target rods 1, the water mist blowtorch 5 has burner accumulation particles and cannot continue to deposit.
[0215] Comparative Example 7:
[0216] This comparative example can refer to Example 4, except that in step (1) of this comparative example, the raw material SiCl4 is introduced from the raw material pipeline port 8 at a flow rate of 80 g / min and a flow velocity v of 1.5 mm / s. After depositing one quartz target rod 1, the water mist blowtorch 5 shows serious accumulation phenomenon and cannot continue deposition.
[0217] Comparative Example 8:
[0218] This comparative example can refer to Example 4, except that in step (1) of the deposition in this comparative example, the distance L from the nozzle of the deposition torch 7 to the intersection of the axial direction of the deposition torch 7 and the axial direction of the quartz target rod 1 is 0.03 m, which does not satisfy the relationship of L = (0.05-0.3) × v. Because the deposition distance is too small, the silicon dioxide and airflow generated by the deposition will rebound to the torch, causing blockage and making it impossible to perform deposition.
[0219] Comparative Example 9:
[0220] This comparative example can refer to Example 4, except that in step (1) of the deposition in this comparative example, the angle α formed by the axis of the water mist torch 5 and the ground plane is 60°. During the deposition process, the airflow of the water mist torch 5 easily rises, making it difficult for it to adhere to the powder rod, and deposition cannot be performed.
[0221] In summary, the quartz glass provided by the present invention has a hydroxyl content difference of ≤100 ppm in the axial direction and a hydroxyl content difference of ≤100 ppm in the radial direction, and has a uniform hydroxyl distribution in both the axial and radial directions, so it can be applied to special experimental instruments, aerospace, ultraviolet energy transmission, and nuclear power radiation resistance high technology fields. Further, the quartz glass of the present invention also has a high hydroxyl content, and its hydroxyl content is ≥750 ppm, and has the advantages of large dispersion value and strong radiation resistance, and can especially absorb short-wavelength ultraviolet light and specific wavelength infrared light, and has different applications in fields such as special experimental equipment, aerospace, biomedicine, spectrum measurement, fiber optic gyroscope, and Rayleigh scattering distribution measurement.
[0222] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some or all of the technical features can be replaced by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A quartz glass, characterized in that: The difference of the hydroxyl content of the quartz glass in the axial direction is ≤100 ppm, and the difference of the hydroxyl content of the quartz glass in the radial direction is ≤100 ppm.
2. The quartz glass according to claim 1, characterized in that The quartz glass has a hydroxyl content of ≥750 ppm.
3. A method for preparing the quartz glass according to claim 1 or 2, characterized in that: The steps include: Step 1, introducing saturated water vapor and a mixed gas of silicon source, hydrogen, oxygen and argon into a deposition chamber, and depositing a quartz target rod using an axial vapor deposition method to obtain a powder rod; Step 2, performing a first sintering on the powder rod in a mixed atmosphere of saturated water vapor and oxygen, and performing a second sintering on the powder rod in a mixed atmosphere of saturated water vapor, oxygen and helium to obtain quartz glass; In the step 1, the silicon source has an inlet flow rate of 20-60 g / min and an inlet flow rate of 1.0-2.0 mm / s; In the step 1, the saturated water vapor is introduced into the deposition chamber through a water mist torch; the angle formed between the axis of the water mist torch and the ground plane is α, and α is 30°-55°; In the step 1, the mixed gas is introduced into the deposition chamber through a deposition torch; the distance from the deposition torch mouth to the intersection of the deposition torch axis and the quartz target rod axis is L, in m, the introduction flow rate of the silicon source is v, in mm / s, and the numerical relationship between L and v satisfies L=(0.05-0.3)×v; preferably, L is 0.05-0.6 m; In step 2, the flow rate of saturated water vapor in the first sintering is Q1, in L / min; preferably, Q1 is 10-80 L / min; the flow rate of saturated water vapor in the second sintering is Q2, in L / min, and the speed increase of the flow rate is k2, in L / min. The second sintering is divided into a heating stage and a constant temperature stage, and the heating time of the heating stage is t, in min; Q2, Q1, k2 and The numerical relationship of t satisfies Q2=Q1+k2× t.
4. The preparation method according to claim 3, characterized in that: The deposition conditions include: a pressure of 0.5-3 Pa; and / or, The first sintering conditions include: a temperature of 400-800° C., a pressure of 100-300 Pa, and a time of 24-72 hours; and / or, The conditions of the second sintering include: the temperature in the constant temperature stage is 1250-1500° C., the pressure is 3-5 Pa, and the time is 4-8 hours.
5. The preparation method according to claim 3 or 4, characterized in that: In step 1, the flow rate of saturated water vapor is 10-50 L / min; and / or, In step 1, the flow rate of hydrogen is 60-110 L / min; and / or, In step 1, the oxygen flow rate is 30-120 L / min; and / or, In step 1, the flow rate of argon gas is 10-15 L / min; and / or, In the step 2, the flow rate of helium during the second sintering is 10-50 L / min.
6. The preparation method according to any one of claims 3 to 5, characterized in that: In step 2, the speed increase of the flow rate of saturated water vapor in the second sintering is k2, in units of L / min. min; the heating rate in the second sintering is k1, in °C / min; The numerical relationship between k2 and k1 satisfies k2=(1.2-1.5)×k1; Preferably, k1 is 2-5°C / min, k2 is 2.4-7.5 L / min min.
7. The preparation method according to any one of claims 3 to 6, characterized in that: In the step 1, the horizontal angle between the water mist torch and the deposition torch is θ, and θ is 30°-150°; preferably, θ is 30°-120°.
8. The preparation method according to any one of claims 3 to 7, characterized in that: In the step 1, depositing the quartz target rod by axial vapor deposition method further comprises setting the rotation speed of the quartz target rod to 5-30 r / min; and / or, In the step 1, the deposition of the quartz target rod by the axial vapor deposition method further comprises setting the lifting speed of the quartz target rod to 30-100 mm / h.
9. The preparation method according to any one of claims 3 to 8, characterized in that: In the step 1, the diameter of the powder particles on the powder rod is 40-140 nm.
10. Application of the quartz glass according to claim 1 or 2 or the quartz glass prepared by the preparation method according to any one of claims 3 to 9 in the fields of special experimental equipment, aerospace, ultraviolet energy transmission, and nuclear power radiation resistance.